Habitat Integrity Challenges for the Chinese Alligator Amid Land Occupation by Human: Pathways for Protection - Sun, Ke; Li, Meng; Wang, Ziyi; Sun, Siqing; Yang, Jiayue; Wu, Xiaobing; Pan, Tao (Ecology and evolution, 2025)
ABSTRACT Effective conservation of endangered species necessitates not only the preservation of core habitats but also the enhancement of landscape connectivity. As a critically endangered Crocodylia, the Chinese alligator (Alligator sinensis) strongly relies on the fragmented wetland habitat of the lower area of the Yangtze River. The integrity of its habitat needs evaluating, and the connectivity restoring plan needs designing. In this study, we estimated the suitability of the habitat in the lower area of the Yangtze River using a Maxent model. Then, the potential ecological corridors between each nature reserve were selected by the least‐cost path and circuit theory methods, and the landscape connectivity was analyzed. The results showed that the highly suitable habitat had a low integrity and was fragmented into small pieces by residential areas, farmland, and mountain areas. Four priority ecological corridors (i.e., Xiadu‐Hongxing, Changle‐Zhongqiao, Zhongqiao‐Shuangkeng, and Hongxing‐Shuangkeng) were selected. The land occupation of humans seriously impacts the integrity of the Chinese alligator, and the unsuitable forest and artificial landscapes along the corridors indicate the need for a massive habitat restoration project. The landscape connectivity of the habitat needs to be progressively restored to provide more possibilities for the dispersal of the Chinese alligator. The integrity of the Chinese alligator habitat was low. The man‐made landscape decreased the suitability of the habitat and limited the disposal of the Chinese alligator. Constructing the ecological corridors was difficult due to human activity, long distance, and slow diffusion speed of the alligator.